Pengaruh Media Sosial Instagram Terhadap Keputusan Berkunjung Wisatawan di Taman Wisata Alam Angke Kapuk Jakarta - Namira, Kaziah Alvi; Sulistiyo, Tri Djoko; Rachim, Faiza (Jurnal Pariwisata, Bisnis dan Digital; Vol 2 No 2 (2026): Jurnal Pariwisata, Bisnis dan DigitalDO - 10.30647/jpbd.v2i2.2097, 2026)
This study aimed to analyze the effect of Instagram as a social media platform on tourists' visiting decisions at Taman Wisata Alam Angke Kapuk, Jakarta. A quantitative approach with an associative research design was employed. The study involved 100 respondents selected using the Slovin formula. Data were collected through a Likert-scale questionnaire and analyzed using SPSS version 21, including validity and reliability tests, coefficient of determination, simple linear regression, and t-test. The results indicated that all research instruments were valid and reliable. Instagram had a positive and significant effect on tourists' visiting decisions, with a regression coefficient of 0.760, a t-value of 12.737 (p < 0.001), and a coefficient of determination (R²) of 0.623. These findings suggest that content quality, information delivery, and user engagement on Instagram play important roles in influencing tourists' decisions to visit the destination. Therefore, destination managers are encouraged to optimize digital marketing strategies by providing engaging and consistent content, while future studies should incorporate additional variables to develop a more comprehensive research model. Keywords: Instagram social media, visiting decision, digital marketing, Taman Wisata Alam Angke Kapuk.